Migraine burden and costs in France: a nationwide claims database analysis of triptan users. (3rd July 2019) - Donnet, Anne; Emery, Corinne; Aly, Samia; Allaf, Bashar; Cayre, Fanny; Mahieu, Nicolas; Gourmelen, Julie; Levy, Pierre; Fagnani, Francis
Abstract: Objectives: To estimate the burden of migraine in the population of French patients identified as specific migraine acute treatment users compared to a control group. Methods: A cross-sectional retrospective analysis was performed on the Echantillon Généraliste des Bénéficiaires claims database, a 1/97 random sample of the French public insurance database. A representative sample of all adults with at least one delivery of triptans, ergot derivatives or acetylsalicylic acid/metoclopramide (all drugs with a specific label in migraine acute treatment – SMAT) in 2014 was selected with a control group matched on age, gender and geographic region. Among triptan users, a sub-group of over-users was defined according to their level of triptan uptake expressed in defined daily doses (DDD – a standard daily dose of treatment of acute migraine) per month over 3 months and more, was also compared with controls. The cost analysis was performed in a societal perspective for direct costs. Sick leave indirect costs were estimated using the human capital approach. Results: In total 8639 SMAT users (mean age: 44.6 years; 78.7% women) were selected representing a crude prevalence rate of 1.7%. The annual per capita total healthcare expenditures were higher by €280 in this group compared to controls (€2463 vs. €2183). Triptans contributed 47.8% to this extra cost. They used significantly ( p < .0001) more frequently than controls antidepressants (20.8% vs. 11.0%), anxiolytics (29.4% vs. 18.8%) and analgesics (53.8% vs. 35.8%). The per capita annual productivity loss associated with sick leave was higher by €295 (€1712 vs. €1417). Among triptan users, there were 2.9% over-users. This last group was characterized by substantially higher per capita annual extra direct (+ €1805) and indirect costs (productivity loss +€706) compared to controls. Conclusions: Due to its high prevalence, migraine costs generate a significant societal burden. The group of over-users concentrates high per capita direct and indirect costs.